Interleukin-6 and IL-6 receptor cell expression in testis of rats with autoimmune orchitis - Rival, Claudia (2006)
Experimental autoimmune orchitis (EAO) is an organ-specific model of autoimmunity characterized by an interstitial lymphomononuclear cell infiltrate as well as sloughing and apoptosis of germ cells. EAO was induced in adult male Sprague-Dawley rats by active immunization with testicular homogenate and adjuvants. Rats injected with saline solution and adjuvants were used as control group. The aim of this work was to study the expression of interleukin-6 (IL-6) and its receptor (IL-6R) in the testis of rats with EAO and analyze whether IL-6 could be involved in germ cell apoptosis. By immunohistochemistry, we detected IL-6 expression in testicular macrophages and Leydig cells of control and EAO rats. Sertoli cells showed IL-6 immunoreactivity in most of the seminiferous tubules of control rats, while a few IL-6+ Sertoli cells were found in the testis of rats with EAO. IL-6R immunoreactivity was observed in macrophages, Leydig and germ cells. A significant increase was noted in the number of IL-6R+ germ cells in rats with EAO compared to control rats. The content of IL-6 (ELISA) in the conditioned media obtained from testicular macrophages of rats with orchitis was significantly higher than in the control group. By immunofluorescence performed on isolated testicular macrophages, IL-6 was shown to be expressed by monocytes recently arrived from circulation (ED1+ cells), while resident macrophages (ED2+ cells) were negative. In vitro experiments (trypan blue and MTS assays) showed that IL-6 (50 ng/ml) reduced germ cell viability. We demonstrated also using the TUNEL technique that IL-6 added to cultures of seminiferous tubule segments induced apoptosis of germ cells. Our results suggest that IL-6 and IL-6R may be involved in the pathogenesis of autoimmune orchitis by promoting testicular inflammation and germ cell apoptosis.